MODELLING AND ANALYSIS OF THE BUS PRIORITY IMPLEMENTATION - Lydia Hidayati (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2012)
Bus is expected to play an important role in providing a reliable travel in congested conditions. Therefore, it has been widely studied to minimize the travel time and the delay of the bus by proposing bus priority scheme to increase the attractiveness of public transport against private vehicles. Signal timing optimization combined with the bus priority scheme are discussed in this research as the alternatives to improve the intersection performances. Further, identifying the effects of these alternatives towards the general vehicles and public transport system performances were the aims of this research as well. As the result of this research, bus advance area with pre-signal method is able to reduce the travel time and delay of the bus for routes 2A and 3A by 11%, 23% and 14% , 0% respectively and able to reduce travel time, delay, and queue of vehicles by 25%, 26%, 7% consecutively. Thus bus advance area with pre-signal method is proposed as the best alternative due to its impact to reduce the bus travel times and delay without degrading the other vehicles performance. Keywords: bus priority, optimizing signal timing, Aimsun simulation, travel time-delay-queue.